2015
DOI: 10.3233/ves-150552
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous inversion of nystagmus without a positional change in the horizontal canal variant of benign paroxysmal positional vertigo

Abstract: The coexistence of cupulolithiasis and canalolithiasis appears to be a possible mechanism of the spontaneous inversion of positional nystagmus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…For the explanation of SRPN in BPPV, several hypotheses have been previously proposed, which included the elastic force of cupula or the gravitational forces of otoconia debris, coexistence of cupulolithiasis, and short-term adaptation of VOR (4,7,(9)(10)(11)14). In our study, given long duration of the reversed phase of positional nystagmus, no significant correlation between nystagmus intensities in the first and reversed phases, and immediate disappearance of reversed nystagmus after treatment of canalolithiasis in most patients, the SRPN in BPPV may be ascribed to short-term central adaptation rather than peripheral mechanical forces or coexistence of cupulolithiasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the explanation of SRPN in BPPV, several hypotheses have been previously proposed, which included the elastic force of cupula or the gravitational forces of otoconia debris, coexistence of cupulolithiasis, and short-term adaptation of VOR (4,7,(9)(10)(11)14). In our study, given long duration of the reversed phase of positional nystagmus, no significant correlation between nystagmus intensities in the first and reversed phases, and immediate disappearance of reversed nystagmus after treatment of canalolithiasis in most patients, the SRPN in BPPV may be ascribed to short-term central adaptation rather than peripheral mechanical forces or coexistence of cupulolithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…(A) After head turning to the right, 3D-video oculography shows vigorous right-beating nystagmus with maximal slow phase velocities of about 140 • /s which decays during 20 s, and then is followed by small left-beating nystagmus lasting more than 60 s. (B) Right Dix-Hallpike maneuver induces upbeat nystagmus with maxSPVs of 50 • /s and rapidly decays during 15 s. Small downbeat nystagmus immediately follows and lasts for 25 s. LH, Horizontal position of the left eye; LV, Vertical position of the left eye. (4,(7)(8)(9)(10)(11). A few studies have described high frequency (73%) of SRPN in HC-BPPV canalolithiasis, whereas the frequency was significantly low (4%) in PC-BPPV (11).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Besides, it has been reported in bilateral cases that reversed nystagmus seen during head turning to healthy side is usually less intense [8,9]. Ogawa, et al [11] reported seven cases (five bilateral and two ipsilateral) with reversal of nystagmus and proposed the possibility of coexistence of canalolithiasis and cupulolithiasis to explain the pathological mechanism for bilateral and unilateral cases. They have indicated that the debris circulating in the long arm of pathological horizontal canal and at the same time, debris entering the non-ampullary side and sinking to the cupula will cause bilateral or unilateral occurrence of reversing nystagmus.…”
Section: Discussionmentioning
confidence: 99%
“…The procedures were in accordance with the ethical standards of the declaration of Helsinki and of institutional review board of the Anadolu Medical Center. Table 1 shows detail analysis of previous nine studies in chronological order [4][5][6][7][8][9][10][11][12].…”
Section: Methodsmentioning
confidence: 99%